The effects of health shocks on family status: do financial incentives encourage marriage? - Andree Ehlert (The European Journal of Health Economics, 2021)
This paper asks whether marriage decisions of unmarried mature couples are driven by the prospect of financial advantages for the later widowed after one partner has suffered a serious health shock. We hypothesize that, in contrast to traditional marriage models, such health shocks may induce unmarried couples to obtain economic benefits, such as survivors' pensions in particular, through marriage in advance of one partner's death. This question has not yet been studied empirically. Hazard models capturing unobserved effects are applied to longitudinal data of the German Socioeconomic Panel. It turns out that the probability of marriage after male partners' health shocks can increase significantly depending on the amount of expected survivors' pensions for the (likely) surviving female partners. In contrast, an increased probability of marriage after health shocks to women (depending on the expected financial benefits to men) was not found. These findings are supported by various robustness checks. Economic and political implications are discussed and the results are placed in an international context.
Keywords: C40; D10; H55; I10; 610; Health shock; Marriage; Survivor's pension; Widow; Old-age poverty; Unobserved heterogeneity; Frailty; Hazard model; SOEP; Germany